Depth variations as effective indicators for strength variation of Najran granites, Najran region, Saudi Arabia - Abd El Aal, Ahmed; Al Zamana, Yahya; Dunquwah, Turki; Alsalmi, Omar; Hussain, Jabir; Iqbal, Javed; Mohamedsalih, Moustafa Abdulrahim; Radwan, Ahmed E.; Al-Awah, Hezam (Frontiers in Materials, 2025)
Igneous rocks of various types are used for various purposes; however, their use as building stones for construction is ubiquitous due to their durability, hardness, appearance, and availability. This study thoroughly examines the impact of the petrographic and physico-mechanical characteristics of Najran granite on the rocks strength with depth variation. In this study 55 granite samples were acquired from various localities in the Najran area, and the various properties were analyzed including petrophysics, and geo-mechanics in reference to various burial depths of 0, 5, 10, 20, 25, and 30 m. Experimental models were constructed to delineate the link the burial depth and mechanical attributes, and then four specimens with different burial depths validated the experimental models. The results depict the direct relationship of mechanical attributes of rocks (i.e., SDI, Brazilian strength, uniaxial compressive strength (UCS), and tensile strength) with increase in burial depth. As the specimen depth increases from 0 to 30 m, the SDI, Brazilian strength, UCS, and tensile strength also increases from 98.67%, 16.65, 132, and 10.82 MPa to 99.76%, 20.46, 187, and 15.33 MPa, respectively. Moreover, the p-wave also increases with the increase in depth, indicating low porosity, voids, and high density. This observation is also confirmed by the low water absorption that decreases with depth as well. Analyses of XRF data also considered the mechanical reasons for the strength with burial depth effects; findings suggested a direct relationship between burial depths and UCS values and inverse relationship with quartz content. For a better knowledge of the granites throughout the region, it is advised to carry out comparative studies on other granites in Saudi Arabia and create a comprehension model using numerical simulation.